The current state of recruitment and selection process among selected government agencies in Leyte - Bravo, Ruchelle; Cabreros, Lara Crianne; Tadea, Dana Mae; Tupaz, Venus Andrea; Villanobos, Zarah; Exconde, Amy Joan E. (2016)
This research aims to assess the current recruitment and selection process among the selected government agencies in Leyte and determine whether they are conforming to the standards set by the Civil Service Commission (CSC). The findings of this study revealed that not all standards set by the CSC on recruitment and selection process are strictly followed by the selected government agencies. Strict compliance of the standards was not observed that resulted to significant discrepancies. Major concerns arose such as the lack of evaluation after the implementation of the recruitment and selection process, too much reliance on referrals failing to promote open competition, not administering qualifying exams to all applicants, and many more trepidations. Adverse to the results, majority of the respondents believed that the hiring process was fair and said that they were satisfied with the current recruitment and selection process of their agency.
Undergraduate research (Bachelor of Science in Management) -- University of the Philippines, Tacloban.
Keywords: Recruitment and selection process